Large‐Amplitude piezoelectric properties of KNbO−3‐based lead‐free ferroelectric ceramics. Issue 3 (15th February 2013) - Nagata, Hajime; Takenaka, Tadashi
Abstract High‐power piezoelectric characteristics of Mn‐ doped KNbO3 (KN + MnCO3 at x wt%, x = 0 to 0.8 wt%, KN‐Mnx) ceramics are reported for the first time in this paper. The mechanical quality factor Qm of KN‐Mnx ceramics at small‐amplitude vibration increased with the Mn content, and the Qm of KN‐Mn0.8 ceramic reached about 820. The maximum vibration speed vo−p, about 2.3 ms, was obtained for KN‐Mn0.8 with Qm = 820. Qm for large‐amplitude vibration in KN‐Mn0.8 and Pb(Zr, Ti)O3 (PZT)‐based ceramics (N6) decreased with increasing vo−p. Qm of KN‐Mn0.8 was smaller than that of N6 for small‐amplitude vibration. However, for large‐amplitude vibration at which vo−p > 0.6 m/s, the Qm value of KN‐Mn0.8 was larger than that of N6. These results indicate that KN‐based lead‐free piezoelectric ceramics possess superior mechanical stability for large‐amplitude vibration. This is a very good sign for high‐power piezoelectric applications. © 2013 Wiley Periodicals, Inc. Electron Comm Jpn, 96(3): 53–58, 2013; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/ecj.10416